A 0.9-V input PWM DCM boost converter with low output ripples and fast load transient response based on a novel square-root voltage mode (SRVM) control approach - Luo, Hao (2021)
A voltage mode DCM boost converter with a square-root voltage mode (SRVM) controller featuring analogue processing is proposed. The controller utilizes as a key parameter the square-root value of the instantaneous load current to obtain pulse-width modulated (PWM) control signals. As a result, no compensation circuits are needed. The output ripples are 0.42% out of the steady-state output of 3 V according to simulation results. Output overshoots of 3 mV with 4 μs recovery time are observed during step-down load transients between 40 and 0 mA in 100 ns. Correspondingly, output undershoots during step-up load transients are less than 10.8 mV with a recovery time of 8.9 μs. The boost converter can start up from its 0.9-V input autonomously based on a proposed two-phase start-up control scheme. In addition, a novel signal boosting technique is presented to ensure gate driving voltages for MOSFET switches as high as attainable to minimize the conduction losses. At the steady state, the boost converter operates with a fixed 1-MHz switching frequency with a 1 μH inductor and a 10 μF capacitor with the maximum load current of 40 mA.